Frugivory and Seed Dispersal by Lizards: A Global Review - Valido, Alfredo; Olesen, Jens M. (Frontiers in Ecology and Evolution, 2019)
Birds and mammals are the only vertebrates which receive comprehensive attention in studies of dispersal of fleshy-fruited plant species. However, recently the importance of fleshy fruit in the diet of lizards (order Squamata: suborder Sauria), and the role of lizards as seed dispersers have been recognized in a number of studies, especially in studies from arthropod-poor habitats such as oceanic islands. Here, we revisit the evidence of fruit-eating lizards on a global scale in order to test if fruit consumption is more common on islands than expected by chance. We constructed a database of 470 lizard species (from a global count of 6,515 species), that have been reported to consume fleshy fruits. This set of lizards belong to 27 families with Scincidae (N= 78 species), Gekkonidae (69), and Dactyloidae (55) having more frugivorous species than other lizard families. We found that 62.4% of these lizards inhabit islands, whereas only one third (35.3%) of all lizard species inhabit on islands. These values support the presence of an ‘insular phenomenon’, however, we also tested if this biogeographical pattern might be driven by body size and evolutionary history of lizards. Thus, we looked for any phylogenetic signals in the distributions of lizard body size, island-presence, and frugivory and calculated phylogenetically corrected correlations among the three variables on a global subset of 2,417 lizard species for which we had detailed phylogenetic information. Both lizard body size and island-presence were weakly influenced by phylogeny; whereas, frugivory was not. In addition, we found that (1) body size and frugivory were weakly positively correlated; (2) body size and island-presence were uncorrelated; and (3) island-presence and frugivory were strongly positively correlated. Thus, we conclude that the main driver of frugivory on islands is the specific island environment and not lizard body size per se. Islands are said to be poor in arthropods and predators, and this may force/allow island lizards to forage for additional food sources such as fleshy fruits. We also suggest that modern lizards as well as their ancestors may potentially play an important role to many plants as seed dispersers.